The effect of circumcision on the frequency of urinary tract infection, growth and nutrition status in infants with antenatal hydronephrosis. (23rd August 2013) - Kose, Engin; Yavascan, Onder; Turan, Ozlem; Kangin, Murat; Bal, Alkan; Alparslan, Caner; Sirin Kose, Seda; Kuyum, Pinar; Aksu, Nejat
Abstract: The objective of this study was to determine the effect of circumcision on the frequency of urinary tract infection (UTI), growth development, and the nutrition status in infants with antenatal hydronephrosis (AH). The data were collected prospectively between 1998 and 2010. Infants with a fetal pelvis diameter of >5 mm identified with antenatal ultrasound were followed-up. Body height and weight were expressed as HZ scores (observed height − median height/standard deviation) and WZ scores (observed weight − median weight/Standard deviation). The nutritional status was evaluated and the body weight was transformed to a weight-for-height index (WHI = weight/median weight for the height age × 100). The HZ and WZ scores or WHI were calculated for each patient at the first and last visits. The chi-square and Student's t tests were used for statistical analysis. A p value <0.05 was considered significant. The study included 178 (134 males, 44 females) patients. Of these, 29 were diagnosed by vesicoureteral reflux (VUR), 87 by obstructive uropathy, and 54 by normal. Of 134 males, 111 infants were circumcised. The mean monitoring time was 45±24.9 months and the mean age of circumcision was 14 ± 16.06 months. The pre-circumcision UTI frequency (2.97 ± 1.14/y) was significantly higher than post-circumcision period (0.25 ± 0.67/y) ( p < 0.05). Also, pre-circumcision UTI frequency (2.97 ± 1.14/y) was significantly higher than the UTI frequency observed in female cases (0.85 ± 0.91/y) and in the overall study group (0.73 ± 0.79/y) ( p < 0.05). In all patients, the HZ of the circumcised subjects (0.18 ± 1.01) was statistically higher than uncircumcised subjects (−0.26 ± 0.92) ( p < 0.05). Although statistically insignificant, the HZ of the circumcised males (0.13 ± 1.24) with VUR was higher than the uncircumcised patients (0.03 ± 0.55) ( p > 0.05). In obstructive uropathy groups, the HZ of the circumcised males (−0.13 ± 0.54) was also found to be higher than uncircumcised males (−0.49 ± 0.66) ( p < 0.05). Although nutrition scores were found to be better in circumcised males, no statistically significant effect of circumcision on the nutrition status was detected. In conclusion, postnatal early circumcision of infants with AH seems to prevent frequent UTIs and nutritional disturbances enabling normal growth.